Drop out from Wanganui Regional Community Polytechnic, 1992-1993 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Administration, Massey University - Coutts, Christine Elizabeth (Massey University, 1995)
In New Zealand recent changes in legislation have increased both the autonomy and accountability of the tertiary education sector. As a consequence, polytechnics have become painfully aware of the cost of student drop out from programmes both to their credibility as quality education providers and to their coffers. The case study of student drop out from Wanganui Regional Community Polytechnic (WRCP) was undertaken in response to administrators' concerns that, as a small, recently established polytechnic, costs associated with the loss of students might threaten its economic viability. WRCP administrators feared an increase in the rate of drop out as changes to the funding of tertiary study created increased financial pressures for students. The case Study employed a range of techniques, including a survey of archived information and student questionnaires, augmented by the perceptions gained from informal discussions with staff to ascertain the extent and nature of drop out. Analysis of data collected over a two year period (1992-1993) at WRCP revealed a pattern of drop out in terms of student characteristics, style and timing of withdrawal. Overall it showed that there was little to discriminate between the characteristics of leavers and those who persisted on a course. The two main theoretical conceptualisations of drop out, the 'integration' and 'investment' theories, were found to share the assumption that drop out is the consequence of 'cost/benefit' analysis. However, despite increased fees and reduced allowances for many students, few cited financial reasons for withdrawal. An analysis of students' self-reported reasons for leaving indicated that finances are but one of many factors which affect a students determination of the costs and benefits of continued attendance. Many reasons given were outside the control of the Polytechnic. However, three Polytechnic academic schools were consistent in their reporting of high drop out numbers, suggesting the need for further research into programme related reasons for withdrawal in these areas. These findings were consistent with recent models, which portray drop out as a complex process influenced by a multitude of factors, including student background and characteristics on entry, environmental changes and institutional factors. From those findings some strategies to enhance the 'fit' of students and hence improve their retention are suggested. Continued monitoring and further research of a more phenomenological nature are recommended in order to gain a greater understanding of student drop out.
Keywords: Wanganui Regional Community Polytechnic; Students; Dropouts; Vocational school dropouts; New Zealand; Wanganui